OP36 Risankizumab therapy induces improvements in endoscopic endpoints in patients with Moderate-to-Severe Crohn's Disease: Results from the phase 3 ADVANCE and MOTIVATE studies. (27th May 2021) - Bossuyt, P; Ferrante, M; Baert, F; Danese, S; Feagan, B G; Loftus Jr, E V; Panés, J; Peyrin-Biroulet, L; Ran, Z; Armuzzi, A; D'Haens, G R; Song, A; et al.
Abstract: Background: Endoscopic healing has become a critical treatment target in Crohn's disease (CD). Risankizumab (RZB), a humanized immunoglobulin G1 monoclonal antibody against the p19 subunit of interleukin 23, is being investigated as a treatment for moderate-to-severe CD. This analysis assessed different endoscopic endpoints in patients treated with RZB induction therapy in two double-blind, randomised, placebo (PBO)-controlled studies (ADVANCE [NCT 03104413 ] and MOTIVATE [NCT 03105128 ]). Methods: Patients with moderate-to-severe CD (CD Activity Index [CDAI] of 220–450, Simple Endoscopic Score for CD [SES-CD] ≥ 6 [≥ 4 for isolated ileal disease] excluding the narrowing component, and average daily [liquid/very soft] stool frequency [SF] ≥ 4 and/or average daily abdominal pain [AP] score ≥ 2) who had demonstrated prior inadequate response or intolerance to conventional and/or biologic treatment (ADVANCE) or to biologic treatment (MOTIVATE) were randomised 2:2:1 (ADVANCE) or 1:1:1 (MOTIVATE) to receive intravenous (IV) RZB 600 mg, RZB 1200 mg, or PBO at weeks 0, 4, and 8. This analysis evaluated the proportion of patients who achieved endoscopic remission ulcer-free endoscopy (ie, absence of ulcers), and composite endpoints of CDAI clinical response and endoscopic response, and enhanced clinical response and endoscopic response at week 12 (endpoints defined in Figure 1 footnotes). All endoscopies were centrally read by a blinded reviewer. Safety was assessed throughout the studies. Results: In ADVANCE and MOTIVATE, 850 and 569 patients, respectively, were randomised and included in the intent-to-treat population for this analysis. At week 12 greater proportions of RZB- vs PBO-treated patients in both studies achieved endoscopic remission ( P ≤ .001), ulcer-free endoscopy ( P ≤ .01), CDAI clinical response and endoscopic response ( P ≤ .001), and enhanced clinical response and endoscopic response ( P ≤ .001; Figure 1 ). Treatment with RZB 600 mg or 1200 mg was well tolerated, and no new safety risks were identified. 1, 2 Conclusion: Induction therapy with IV RZB 600 mg or 1200 mg resulted in improved outcomes at week 12 compared with PBO as assessed by endoscopy and by composite endoscopic-clinical endpoints in patients with moderate-to-severe CD. References: D'Haens G et al. ADVANCE study. Abstract presented at Digestive Disease Week 2021; 21–23 May 2021; Virtual. AbbVie In. (7 Jan 2021). Risankizumab (SKYRIZI®) Demonstrates Significant Improvements in Clinical Remission and Endoscopic Response in Two Phase 3 Induction Studies in Patients with Crohn's Disease [Press release]. Retrieved from https://news.abbvie.com/news/press-releases/risankizumab-skyrizi-demonstrates-significant-improvements-in-clinical-remission-and-endoscopic-response-in-two-phase-3-induction-studies-in-patients-with-crohns-disease.htm